Dispositif, format, posture : une méthode d’analyse de l’iconographie géographique - Didier Mendibil (Cybergeo)
This text describes three tools on which a methodical analysis of geographical iconography can be based on and how it works. The pictures chosen formats, the arrangement and the layout of the pictures as well as the iconographic way of commenting them, strongly help to identify iconographic systems. Several practical examples specify this method and its limits in the contemporary history of French geography.